Connections between the residential circumstances and the roma segregation processes in the outskirts of Hajdúböszörmény in the light of empirical examinations - Mező, Barna (Acta Agraria Debreceniensis, 2012)
In addition to the processing of the available special literature, this study aims to provide an accurate view of the segregation processes in Hajdúböszörmény, as well as their effect on the real estate market by interviewing roma people living in Hajdúböszörmény and by getting to know the opinions of the affected professionals and decisionmakers working at the local authorities.